2016
DOI: 10.1139/cjps-2015-0378
|View full text |Cite
|
Sign up to set email alerts
|

Sainfoin (Onobrychis viciifolia Scop.): renewed interest as a forage legume for western Canada

Abstract: Sainfoin (Onobrychis viciifolia Scop.) is a perennial forage legume that has received renewed interest in western Canada because of its desirable forage characteristics. The objective of this review is to summarize previous studies on the agronomy, forage yield, nutritive value, seed characteristics, and diseases and pests of sainfoin. In addition, the review also focuses on the genetic diversity and registered cultivars of sainfoin and their potential use in temperate grasslands. Past studies have reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 52 publications
1
38
0
2
Order By: Relevance
“…have been evaluated in the United States, Canada, New Zealand, and Switzerland (Mosjidis 2001;Waghorn 2008;Häring et al, 2008;Berard et al, 2011;Li et al, 2014;Grabber et al, 2015), sulla in Australia (de Koning et al, 2003(de Koning et al, , 2010Heuzé et al, 2015) and sainfoin in Canada and Europe (Häring et al, 2008;Hayot Carbonero et al, 2011;Malisch et al, 2015;Bhattarai et al, 2016). have been evaluated in the United States, Canada, New Zealand, and Switzerland (Mosjidis 2001;Waghorn 2008;Häring et al, 2008;Berard et al, 2011;Li et al, 2014;Grabber et al, 2015), sulla in Australia (de Koning et al, 2003(de Koning et al, , 2010Heuzé et al, 2015) and sainfoin in Canada and Europe (Häring et al, 2008;Hayot Carbonero et al, 2011;Malisch et al, 2015;Bhattarai et al, 2016).…”
Section: Agronomy Weed Control Harvesting and Processing Of Tanninmentioning
confidence: 99%
“…have been evaluated in the United States, Canada, New Zealand, and Switzerland (Mosjidis 2001;Waghorn 2008;Häring et al, 2008;Berard et al, 2011;Li et al, 2014;Grabber et al, 2015), sulla in Australia (de Koning et al, 2003(de Koning et al, , 2010Heuzé et al, 2015) and sainfoin in Canada and Europe (Häring et al, 2008;Hayot Carbonero et al, 2011;Malisch et al, 2015;Bhattarai et al, 2016). have been evaluated in the United States, Canada, New Zealand, and Switzerland (Mosjidis 2001;Waghorn 2008;Häring et al, 2008;Berard et al, 2011;Li et al, 2014;Grabber et al, 2015), sulla in Australia (de Koning et al, 2003(de Koning et al, , 2010Heuzé et al, 2015) and sainfoin in Canada and Europe (Häring et al, 2008;Hayot Carbonero et al, 2011;Malisch et al, 2015;Bhattarai et al, 2016).…”
Section: Agronomy Weed Control Harvesting and Processing Of Tanninmentioning
confidence: 99%
“…As a consequence of the apparent differences in agronomic performance and CT concentration associated with genetic stock, many researchers have begun their studies by first obtaining seeds from globally diverse populations (Azuhnwi et al, 2011(Azuhnwi et al, , 2012Bhattarai, Coulman, Fu, Beattie, & Biligetu, 2017;Gea, Stringano, Brown, & Mueller-Harvey, 2011;Goplen, Howarth, Sarkar, & Lesins, 1980;Hatew et al, 2015aHatew et al, , 2015bHosaininejadmir, Jafari, & Nakhjavan, 2011;Jafari, Rasouli, Tabaei-Aghdaei, Shanjani, & Alizadeh, 2014;Lorenz, Carbonero, Smith, & Udén, 2012;Malisch et al, 2015;Mohajer et al, 2013;Prospéri, Demarquet, Angevain, & Mansat, 1994;Thill et al, 2012;Zarrabian, Majidi, & Ehtemam, 2013). This reflects an attempt to rapidly enhance research efforts on sainfoin by utilizing advanced techniques, in part due to new interest in potential environmental and animal health benefits.…”
Section: G Ene Ti C Re Source Smentioning
confidence: 99%
“…It is a cross‐pollinated crop with each inflorescence containing 70–80 pink or purple flowers (Goplen, Richards, & Moyer, ). A review on sainfoin origin, adaptation, agronomy and its genetic diversity can be found in Bhattarai, Coulman, and Biligetu ().…”
Section: Introductionmentioning
confidence: 99%
“…A number of sainfoin cultivars have been released for use in temperate regions, but genetic improvement is relatively slow due to the lack of adapted germplasm and limited breeding effort (Bhattarai et al., ). Characterization of new germplasm is critical to plant breeding because it not only provides phenotypic and agronomic information, but also is useful for estimation of genetic variation for further genetic selection (Govindaraj, Vetriventhan, & Srinivasan, ).…”
Section: Introductionmentioning
confidence: 99%